Outpatient Registration Information System with Cloud Computing Storage at Candipuro Health Center, Lumajang Regency - Firda Latifani Pertiwi (JURNAL MEDICAL P-ISSN : 2685-7960 e-ISSN : 2685-7979, 1970)
Based on the Regulation of the Minister of Health of the Republic of Indonesia Number 44 Year 2016 regarding the Guidelines for Public Health Center Management, it is explained that the Public Health Center known as Puskesmas is the First Level Health Facility (FKTP) responsible for public health in its working area in one or part of the subdistrict area. In performing its duties and functions, it must implement Public Health Center management effectively and efficiently. The cycle of quality Puskesmas management is a continuous series of routine activities, carried out in the implementation of quality health efforts, which must be monitored periodicly and regularly, supervised and controlled over time, in order to repair and improve performance. The error that can be found at Candipuro Public Health Center is that there is no system that loads related to the search of patient database so that it makes redundancy for patients who seek treatment when the old patient's word can not be found. With the advantages in the Public Health Center is a computer facility on every poly and service units, as well as adequate internet access. To support this research, data collecting method is done by observation, interview, literature study, analysis, system design, system building, testing and system implementation.